1997
DOI: 10.1046/j.1365-2435.1997.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of temperature on the web‐building behaviour of the common house spider, Achaearanea tepidariorum

Abstract: Summary 1.Because spiders are ectothermic animals, the temperature regime of the microhabitat in which an individual finds itself may affect important performance traits of that individual. The present study examined the effects of temperature on attributes of webs spun by Achaearanea tepidariorum (C. L. Koch), as well as testing temperature preference in this species. The effects of temperature on the amount of silk per web produced by Achaearanea tepidariorum and the prey-capture efficiency of webs produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…In fact, the dependency of spider webs on environmental and physiological conditions is not exclusive of orb-weavers. Barghusen et al (1997) suggested that Achaearanea tepidariorum C.L. Koch (Araneae: Theridiidae), an aerial space web builder (Uetz et al, 1999) optimizes web construction by temperature selection and found an optimal experimental temperature at 20°C at which the spiders produced the heaviest webs and prey capture should be maximized.…”
Section: Bioecological Interpretation Of the Effect Of Temperature Onmentioning
confidence: 99%
“…In fact, the dependency of spider webs on environmental and physiological conditions is not exclusive of orb-weavers. Barghusen et al (1997) suggested that Achaearanea tepidariorum C.L. Koch (Araneae: Theridiidae), an aerial space web builder (Uetz et al, 1999) optimizes web construction by temperature selection and found an optimal experimental temperature at 20°C at which the spiders produced the heaviest webs and prey capture should be maximized.…”
Section: Bioecological Interpretation Of the Effect Of Temperature Onmentioning
confidence: 99%
“…The use of webs for foraging and the role that trapping threads play in catching prey have been described several times (see, e.g., Nielsen 1932;Szlep 1965;Foelix 1996;Barghusen et al 1997;Griswold et al 1998). Szlep (1965) has found that A. tepidariorum spin webs that closely resemble those of the Mediterranean Black Widow spider Latrodectus tredecimguttatus (Rossi).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the present paper regard this phase of wrap attack, in which the prey is not rotated as it is wrapped, as a continuation of immobilization wrapping described above. A. tepidariorum is known for capturing crawling prey when the prey encounters the viscid vertical capture threads of the web (Barghusen et al 1997). Like other theridiids, it also hunts prey, which breaks trapping threads with its own movement and is subsequently catapulted into the air or, more exactly, into the web, where both immobilization wrapping and the first contact between the spider and the prey occur.…”
Section: Discussionmentioning
confidence: 99%
“…A. keyserlingi occurs along the east coast of Australia and is commonly found in urban habitats such as gardens and parks. As abiotic factors such as wind, temperature and relative humidity may influence web design in spiders (Barghusen et al 1997;Vollrath et al 1997) both experiments were performed under controlled laboratory conditions.…”
Section: Methodsmentioning
confidence: 99%